Stocktaking the Fund's Engagement with Regional Financing Arrangements. (Policy Papers; Policy Paper ;, 2013)
Following the global financial crisis of 2008-09, regional financing arrangements (RFAs) have been recognized as an important layer of the global financial safety net. This paper summarizes the current landscape of RFAs, and discusses IMF-RFA coordination to date and options for enhancing cooperation going forward. In so doing, it intends to contribute to discussions underway at international fora and solicit views from the Fund and RFA memberships on how to enhance cooperation.